Spatial and temporal effects on hydraulic conductance and other attributes of bamboo (Gigantochloa scortechinii Gamble) - Mohamed, Johar (2019)
Gigantochloa scortechinii Gamble (Buluh Semantan) is one of the most common bamboo species, and abundant with scattered distribution in Peninsular Malaysia. A study was initiated to determine the structure and variation of most ignored part which is rhizome from three different study sites and four consecutive rhizome ages. The study focused on the variation of physiological, anatomical, chemical, and phytochemical attributes in relation to site and rhizome age. This study was conducted at three different locations of Peninsular Malaysia, namely Amanjaya Forest Reserve (Perak), Kenaboi Forest Reserve (Negeri Sembilan), and Ayer Hitam Forest Reserve (Selangor). The sites were selected due to abundant of G. scortechinii bamboo species distribution at those areas, and also represented different climatic condition such as elevation, precipitation, and temperature. The destructive sampling of four consecutive rhizomes of the bamboo species G. scortechinii was conducted using selective random sampling method from healthy clumps. The four consecutive rhizomes were represented as four different rhizome ages: a) new sprout, b) young, c) premature, and d) mature rhizome.